TRANSFORMING LOCAL ECONOMIES THROUGH WOMEN-LED MICRO ENTERPRISES IN VIKSIT BHARAT - S, Ruby; V, Vijila; H, Sajeev; M, Anilkumar. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the function of Local Self-Government Institutions (LSGIs) in facilitating forward-thinking micro-enterprises managed by women to stimulate local development. This study analyses the adoption and diffusion of innovations among these firms using the framework of Innovation Diffusion Theory. To evaluate the influence of LSGI efforts on women's entrepreneurship and community development, a conventional theme analysis is performed, which specifically examines personal, production, money, labour, marketing issues, and innovation potential. The Innovation Diffusion theory is a significant and influential factor in the growth of enterprises and the societal welfare of women. The results illustrate the substantial influence of Kudumbashree WME on the process of societal change, by promoting the advancement of local women and thereby contributing to the well-being of Kerala. The study confirms the practical significance of Innovation Diffusion in empowering micro-organisations led by women with the assistance of Local Self-Government Institutions (LSGIs).